Diagnostic Performance of Rapid Antigen Testing for SARS-CoV-2: The COVid-19 AntiGen (COVAG) study - Wertenauer, Christoph; Brenner Michael, Geovana; Dressel, Alexander; Pfeifer, Caroline; Hauser, Ulrike; Wieland, Eberhard; Mayer, Christian; Mutschmann, Caren; Roskos, Martin; Wertenauer, Hans-Jörg; Moissl, Angela P.; Lorkowski, Stefan; et al. (Frontiers in Medicine, 2022)
Background: Widely available rapid testing is pivotal to the fight against COVID-19. Real-time reverse transcription-polymerase chain reaction (rRT-PCR) remains the gold standard. We compared two frequently used commercial rapid diagnostic tests (RDTs) for SARS-CoV-2-antigens, the SD Biosensor SARS-CoV-2 Rapid Antigen Test (Roche Diagnostics) and the Panbio COVID-19 Ag Rapid Test (Abbott Diagnostics), against rRT-PCR for SARS-CoV-2 detection. Methods: We compared the tests in 2215 all-comers at a diagnostic centre between February 1 and March 31, 2021. rRT-PCR-positive samples were examined for SARS-CoV-2 variants. Findings: 338 participants (15%) were rRT-PCR-positive for SARS-CoV-2. The sensitivities of Roche-RDT and Abbott-RDT were 60.4% and 56.8% (P<0·0001) and specificities 99.7% and 99.8% (P=0·076), respectively. Sensitivity inversely correlated with rRT-PCR-derived Ct values. Unadjusted, the RDTs had higher sensitivities in individuals referred by treating physicians and health departments than those tested for other reasons, in persons without comorbidities compared to those with comorbidities, in individuals with symptoms suggesting COVID-19, and in the absence of SARS-CoV-2 variants compared to Alpha variant carriers. The associations of sensitivity with clinical symptoms and the SARS-CoV-2 genotype were robust against adjustment for Ct values. Assuming that 10 000 symptomatic individuals are tested, 500 of which are truly positive, the RDTs would generate 38 false-positive and 124 false-negative results. Assuming that 10 000 asymptomatic individuals are tested, including 50 true positives, 18 false-positives and 34 false-negatives would be generated. Interpretation: The sensitivities of the two RDTs for asymptomatic SARS-CoV-2 infected patients are unsatisfactory. This calls into question whether their widespread use is effective in the ongoing SARS-CoV-2 pandemic. The virus genotype influences the sensitivity of the two RDTs. Therefore, the sensitivity of RDTs should be evaluated separately for different SARS-CoV-2 variants.